The Privacy of public companies in Iraq: a comparative study - Abdullah, Ragad; Mohammed, Rasha (Journal of Legal Sciences, 2022)
General companies are one of the methods that help managing general economic services. Countries have taken a step into this type of management because of the criticism-related to the different styles of managements. Criticism have been directed specifically at the direct type of management to such general economic services. Most of the Iraqi economic general services are being ran by this type of style; general type.What has been agreed upon, whether in France, Egypt or Iraq has been that such establishments of general companies have to take place either by legislating a special order that states constructing a general company by the legislator or according to the law by authorizing law by the legislator to one of the local personnel. Such step should occur for the purpose of enabling and establishing a new general company.This type of companies subject to both of public general and private laws. Being subjected to the public general law result from being the two types as general services. On the other hand, when being subjected to the private law will occur executing economical activities similar to the individuals’ attributes.There are my features that the general companies have in which we can summarize by the definition of these companies. The first feature is their ownership to the state (government); legislated by the law frankly speaking.Additionally, they are considered legal personality in which companies can be independent away from the government or the person who owns it. Moreover, they face financial and administrative interdependence, as well as relying upon self-financing.